STRATEGI PT HUMPUSS MARITIM INTERNASIONAL DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS POIN 14 DI INDONESIA TAHUN 2024 - Azzahra, Jamila; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to identify the strategy of PT Humpuss Maritim Internasional (HUMI) in supporting Sustainable Development Goals (SDGs) point 14 on life below water through the implementation of the Humpuss Blue Commitment. The research employs a qualitative descriptive method using interviews and literature review. The findings show that HUMI’s strategy is implemented through proper ballast water management, the use of Oil Water Separator (OWS) technology, improved ship waste management, and environmental initiatives such as mangrove planting and employee awareness programs. The implementation of these strategies has strengthened environmental compliance within the company, as reflected in the absence of violations in 2024. However, the company still faces challenges in building sustainability awareness among employees, which continue to be addressed through policy reinforcement and ongoing innovation. Keywords: PT Humpuss Maritim Internasional, Sustainable Development Goals, Life Below Water.